Psychometric Performance of Resilience Scale for Chinese Adolescent (RSCA) for Undergraduates in Guangdong, China - Yongmei, Hou; Yiyang, Wang (American Journal of Education and Learning, 2021)
To analyze the psychometric performance of Resilience Scale for Chinese Adolescent (RSCA) for undergraduates in Guangdong. Stratified random sampling method was used to select 1628 undergraduates from 7 colleges in Guangdong. RSCA and Academic Burnout Scale for Chinese Undergraduates (ABSCU) were used to investigate them. Cronbach’s αcoefficient and split-half reliability were used to analyze the internal consistency of RSCA. Convergent validity, discriminant validity, factor analysis and criterion validity were used to evaluate its validity. Celling and floor effect were used to analyze its sensitivity. Cronbach’s α coefficient of the total questionniar, 2 domains and 5 factors were0.72-0.86, which met the requirements of the group comparison. Spearman-Brown split-half coefficient of the total questionniar, 2 domains and 5 factors were 0.71-0.89. The calibration success rate of convergent and discriminant validity of 5 factors were all 100%. The calibration success rate of convergent and discriminant validity of 2 domains were all above 86.7%. Five principal components obtained from 27 items, witha cumulative variance contribution rate of48.79% and two principal components obtained from 5 factors, withacumulative variance contribution rateof 65.23%,which basically metthe theoretical conception of RSCA. The total score of RSCA significantly predicted the total score of ABSCU (Radj2=0.158, P<0.001). The total score, scores of 2 domains and 5 factors of RSCA were all normal distribution, without any celling or floor effect. The psychometric performance of RSCA for undergraduates in Guangdong were valid and reliable.